Proactive career management for female health professionals: a scoping review protocol - Wayne Freeman Chong; Junjie Chua; Li Zi Leong; Helen Elizabeth Smith; Kang Yang Trevor Yu (BMJ Open)
Introduction Many women in frontline healthcare positions face work demands that are incompatible with their needs and aspirations, resulting in poorer work satisfaction and engagement, and greater probability of leaving their jobs. Proactive career management is associated with elevated well-being and career success but may not be accessible to female health professionals who encounter social, cultural and structural barriers. The complex and diverse nature of proactive career management and absence of a comprehensive review on the topic necessitates a synthesis of extant literature. This study aims to identify (i) proactive career management behaviours and activities among female health professionals and (ii) outcomes of proactive career management initiatives. This study will contribute to a larger study on encouraging proactive career management behaviours among Singapore female health professionals.Methods and analyses Scoping review is used as our method of evidence synthesis to provide a comprehensive overview of all available constructs and markers of interest. This study started in January 2022. Original research, reviews, short reports, letters, methodologies and case studies relevant to our objectives will be examined with guidance from Arksey and O’Malley’s framework. The literature contained in scientific databases and grey literature sources will be thoroughly searched. Two independent reviewers will screen citations for eligibility and extract data from the included articles. Extracted data will be narratively synthesised by two independent reviewers using Braun and Clarke’s six steps of thematic analysis. We will observe the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews standards in reporting the results. An advisory panel will provide insights on the applicability of the results to negate confirmation bias.Ethics and dissemination Ethics clearance is not required. Dissemination plans include peer-reviewed journal publication and conference presentations.Registration details This review was registered on open science framework (Registration DOI: https://doi.org/10.17605/OSF.IO/2SY8V).